Comparison between linear model and nonlinear model of magnetically suspended balanced beam (MSBB) - Fijay, Fauzi; Ismail, Daut; Muzamir, Isa; Baharuddin, Ismail (Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO), 2008)
Organized by Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO), 19th - 20th December 2006 at Batu Pahat, Johor.